A new Spectrophotometric Method For The Determination of La (III) With 3-Hydroxy -4-(2-hydroxyPhenyl azo) Naphthalene -1- Sulfonic Acid - Darweesh, S. A.; Hammodi, A. S.; Mahmmod, R. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
A simple, rapid and sensitive spectrophotometric method has been proposed for the determination of La (III) using 3-hydroxy -4-(2-hydroxy-phenyl azo) naphthalene -1- sulfonic acid as a chromogenic reagent. This method is based on the formation of a red-pink colored complex, upon the reaction of La(III) with the reagent in an alkaline medium (pH= 9.50), having a maximum absorbance at 459 nm. Beer’s law is valid in the concentration range 0.512 Âµg.ml-1 with a Sandell’s sensitivity value of 0.0188 Âµg.cm-2 and molar absorptivity of 7376.12 L.mol-1.cm-1. The stoichiometric composition of the chelate is 1:3. The effect of the presence of different cations as interferants in the determination of La(III) under the given optimum conditions were investigated.